2020
DOI: 10.1007/s13246-020-00899-8
|View full text |Cite
|
Sign up to set email alerts
|

Technique, radiation safety and image quality for chest X-ray imaging through glass and in mobile settings during the COVID-19 pandemic

Abstract: The COVID-19 pandemic in 2020 has led to preparations within our hospital for an expected surge of patients. This included developing a technique to perform mobile chest X-ray imaging through glass, allowing the X-ray unit to remain outside of the patient’s room, effectively reducing the cleaning time associated with disinfecting equipment. The technique also reduced the infection risk of radiographers. We assessed the attenuation of different types of glass in the hospital and the technique parameters require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 5 publications
(6 reference statements)
8
45
0
Order By: Relevance
“… 10 Brady and colleagues reported that 30 through-glass radiographs were assessed by 2 readers: one scored 70% of them as acceptable quality while the other scored 90% of them acceptable. 11 However, they did not compare these images to conventionally obtained radiographs. Thus, it cannot be determined if image quality was equivalent.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Brady and colleagues reported that 30 through-glass radiographs were assessed by 2 readers: one scored 70% of them as acceptable quality while the other scored 90% of them acceptable. 11 However, they did not compare these images to conventionally obtained radiographs. Thus, it cannot be determined if image quality was equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the low radiation dose involved in radiography compared to CT makes it an ideal imaging modality for follow-up purposes. 41 In COVID-19 cases, the appearance of lung changes on chest radiography is dependent on the stage of disease. Initially, chest radiographs are usually insensitive to mild changes in patients with early disease; however, at later or more advanced stages, radiograph abnormalities are usually apparent.…”
Section: H E S T R a D I O G R A P H F I N D I N G Smentioning
confidence: 99%
“…The Radiological Society of North America (RSNA) scientific expert review panel proposed an innovative method of obtaining portable or bedside chest radiograph through glass walls of isolation rooms on March 18, 2020 [15] . This technique was subsequently shown to be able to produce diagnostic quality radiographs with no significant increase in radiation to the patient [16] , [17] , [18] , [19] . With some refinements, our hospital quickly adopted this technique.…”
Section: Introductionmentioning
confidence: 99%